2023
DOI: 10.1002/pds.5591
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an electronic health records‐based opioid use disorder algorithm by expert clinical adjudication among patients with prescribed opioids

Abstract: Background: In the US, over 200 lives are lost from opioid overdoses each day.Accurate and prompt diagnosis of opioid use disorders (OUD) may help prevent overdose deaths. However, international classification of disease (ICD) codes for OUD are known to underestimate prevalence, and their specificity and sensitivity are unknown.We developed and validated algorithms to identify OUD in electronic health records (EHR) and examined the validity of OUD ICD codes. Methods: Through four iterations, we developed EHR-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This is an attempt to use ML in the broader health system space to advance this field as others have done within smaller systems 42 , 43 and to improve predictive, clinical analytics. 44 , 45 The importance of this work is that it begins to bridge the gap between systems research and clinical research, with a key next step focus on combining ML and cluster analysis at the system level with individual-level claims and/or electronic medical record data—analyses that the authors believe are essential to bridging the gap between clinical outcomes and key SDOH.…”
Section: Discussionmentioning
confidence: 99%
“…This is an attempt to use ML in the broader health system space to advance this field as others have done within smaller systems 42 , 43 and to improve predictive, clinical analytics. 44 , 45 The importance of this work is that it begins to bridge the gap between systems research and clinical research, with a key next step focus on combining ML and cluster analysis at the system level with individual-level claims and/or electronic medical record data—analyses that the authors believe are essential to bridging the gap between clinical outcomes and key SDOH.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, this study relied on ICD codes available in administrative claims data for OUD identification. Because the specificity and sensitivity of OUD ICD codes are unknown and may lead to under-identification [ 47 ], our estimates would be subject to measurement error and could be attenuated. Further, considering this limitation and recognizing the chronic nature of OUD, our findings could be more accurately interpreted as indicating an increased risk of suicide attempts by opioid poisoning, especially among those women diagnosed with OUD both during pregnancy and postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…Included patients were identified using ICD-10 codes for diagnoses of OUD. Prior studies validating OUD ICD-10 codes have found low (10-40%) sensitivity but high (> 95%) specificity and thus, our study may exclude some patients with OUD (48,49). The PINC AI database provides charge claims only for medications received during inpatient admission.…”
Section: Online Clinical Investigationsmentioning
confidence: 99%